The Effect of Organic Casgot Fertiliziser on Plant Growth and Chlorophyl Levels of Pakchoy (Brassica rapa L.) - Karimah, Multazimatul; Rahmah, Azizatur; Hanifa, Berry Fakhry (El-Hayah:Jurnal Biologi, 2023)
Casgot is one of the organic fertilizers resulting from the bioconversion process of organic waste by maggots and has great potential to provide additional nutrients for Pakchoy. Pakchoy (Brassica rapa L.) is a herbaceous plant with high economic value and market opportunities and a fast growth time. Optimal pakchoy growth is influenced by chlorophyll levels. The nutrient content in casgot will increase chlorophyll formation resulting in increased pakchoy growth. The purpose of this study was to determine the effect of casgot on plant growth and chlorophyll levels of pakchoy (Brassica rapa L.). This research uses descriptive quantitative with a completely randomized design (CRD). The treatments in this study consisted of K1 (positive control), K2 (negative control), A1 (mixed casgot 100 g), A2 (mixed casgot 150 g), B1 (rice casgot 100 g), B2 (rice casgot 150 g), C1 (vegetable casgot 100 g) and C2 (vegetable casgot 150 g). The data analysis used was ANOVA followed by DMRT 5% (Duncan Multiple Range Test) using SPSS. The results showed that the best quality of C, N, P, K and Mg came from casgot with mixed nutrient sources that met the SNI. The treatment of casgot A2 (150 g mixed) gave the best results in all the observed parameters, namely number of leaves (19.66), leaf area (109.68 cm), plant height (24.50 cm), wet weight (197 g), dry weight (13.66) g, and chlorophyll content (73.12 ppm) and gave an equivalent effect to the control treatment with urea.